Sikap Konsumtif Mahasiswa Penerima Beasiswa KIP Kuliah di FKIP Universitas Riau - Melati Melati; Daeng Ayub; Said Suhil (Jurnal Pelita Pengabdian Masyarakat, 2024)
The purpose of this study was to determine the consumptive level of students receiving KIP Lecture scholarships at FKIP Riau University. This research is a quantitative research using a descriptive approach. Validity test with a critical r value of 0.463 obtained from 30 students of FKIP Riau University. Of the 48 statements tested, 6 statements were discarded so that 42 statements were used for research. In accordance with the reliability test analysis using the SPSS version 23.0 program to find the Cronbach's Alpha value and obtained an average value of 0.846 which means that there are 42 valid questionnaire statement items to be used as data collection tools. From the descriptive analysis based on the attitude variable with a mean of 3.77 which is in the high interpretation. The conclusion of this study is that as a result of the research obtained, the Consumptive Attitude of KIP Scholarship Recipient Students at FKIP Riau University is on a high interpretation seen from demographic factors in the gender category and major category with the acquisition of an average mean of 3.74. So it can be interpreted that consumptive attitudes affect the gender and also the majors of students receiving KIP Lecture scholarships at FKIP Riau University.